PSYCHOLOGICAL CAPITAL SEBAGAI PREDIKTOR KECENDERUNGAN NON SUICIDAL SELF INJURY (NSSI) PADA GENERASI Z - Syarofina Izna Maulidah; Miftakhul Jannah (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: Psychological capital can minimize an individual’s tendency to engage in non suicidal self injury (NSSI) behavior, which is a form of non-adaptive coping mechanism. Objective: This research aims to determine the influence of psychological capital on non suicidal self injury (NSSI) tendencies in generation Z. Method: This research uses a non-experimental quantitative method approach. Respondents in the research were generation Z aged 15-27 years in Village X as many as 148 people using random sampling techniques. The instruments used in this research used the PCQ-24 scale and non suicidal self injury tendencies scale. Result: The results obtained show a significance value of 0.000 < 0.05, a correlation coefficient figure of -0.474, an R2 value of 0.225. Conclusion: There is a significant influence of psychological capital on the tendency for non suicidal self injury (NSSI) in Generation Z, where the relationship between the two is opposite, in other words, the higher psychological capital, the lower the tendency for non suicidal self injury